Does the Oral Microbiome Play a Role in Hypertensive Pregnancies? - Willmott, Thomas; McBain, Andrew J.; Humphreys, Gavin J.; Myers, Jenny; Cottrell, Elizabeth (Frontiers in Cellular and Infection Microbiology, 2020)
Chronic hypertension during gestation is associated with an increased risk of adverse pregnancy outcomes including pre-eclampsia, fetal growth restriction and preterm birth. Research into new chemotherapeutic regimes for the treatment of hypertension in pregnancy is limited due to concerns about fetal toxicity and teratogenicity, and new therapeutic avenues are being sought in alternative physiological pathways. Historically, generation of the vasodilator nitric oxide was believed to be solely from L-arginine by means of nitric oxide synthase enzymes. Recently, a novel pathway for the reduction of dietary inorganic nitrate to nitrite by the bacteria in the oral cavity and subsequently to vasodilatory nitric oxide within the body has been uncovered. Dietary nitrate is abundant in green leafy vegetables, including beetroot and spinach, and reduction of exogenous nitrate to nitrite by oral bacteria can increase nitric oxide in the vasculature, lessening hypertension. Supplements rich in nitrate may be an attractive choice for treatment due to fewer side effects than drugs that are currently used to treat hypertensive pregnancy disorders. Additionally, manipulation of the composition of the oral microbiota using pro- and prebiotics in tandem with additional dietary interventions to promote cardiovascular health during gestation may offer a safe and effective means of treating hypertensive pregnancy disorders including gestational hypertension and pre-eclampsia. The use of dietary inorganic nitrate as a supplement during pregnancy requires further exploration and large scale studies before it may be considered as part of a treatment regime. The aim of this article is to review the current evidence that oral microbiota plays a role in hypertensive pregnancies and whether it could be manipulated to improve patient outcomes.